1950
DOI: 10.1002/jcp.1030360306
|View full text |Cite
|
Sign up to set email alerts
|

A cytochemical study of oogenesis and cleavage in the mouse

Abstract: INTRODVCTIONRecent advances in several independent fields of biological research have tended to indicate that the desoxyribose nucleic acid (DXA) of clironiosomes exhibits a number of properties which may be coilsidered essential for the identification of a Iiypothetical genic material. These properties are :1. High specific activity, such as shoxn by the transforming principle of microorganisms (Avery, MacLeod and Mc-Carty, '44 ; Roivin, Delaunay, Vcndrely and Lehoult, '45). 2. RerriarkabIe stability during m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

1954
1954
1981
1981

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(36 citation statements)
references
References 33 publications
5
31
0
Order By: Relevance
“…Nucleoplasmic RNA polymerases which are sensitive to a-amanitin have been found to be active at this stage (Moore, 1975 Knowland and Graham (1972) reported the presence of extremely small amounts of newly labelled rRNA at the 2 cell stage (see also Hillman and Tasca 1969). In the present study the appearance of basophilic material was first observed at the peripheries of the nucleoli of 4 cell embryos (see also Alfert, 1950 ;Flax, 1953). We have previously demonstrated that it was precisely at this location that the activities of the a-amanitin-resistant, type I RNA polymerases reappeared (Moore, 1975).…”
supporting
confidence: 60%
“…Nucleoplasmic RNA polymerases which are sensitive to a-amanitin have been found to be active at this stage (Moore, 1975 Knowland and Graham (1972) reported the presence of extremely small amounts of newly labelled rRNA at the 2 cell stage (see also Hillman and Tasca 1969). In the present study the appearance of basophilic material was first observed at the peripheries of the nucleoli of 4 cell embryos (see also Alfert, 1950 ;Flax, 1953). We have previously demonstrated that it was precisely at this location that the activities of the a-amanitin-resistant, type I RNA polymerases reappeared (Moore, 1975).…”
supporting
confidence: 60%
“…The metabolic activity during the early cleavage stages of mammals differs in several respects from that of the blastocyst : alkaline phosphatase is not present in rat ova (Mulnard, 1955) ; cytoplasmic levels of rna are reduced in mouse and rat eggs as attested by the use of various techniques (Alfert, 1950;Austin & Braden, 1953). The 2-to 8-celled egg in vitro has limited ability to carry out glycolysis in contrast to late morula and blastocyst stages (Fridhandler, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…In the present case the thyroid nuclei of hypophysectomized and normal rats show volumes in a ratio of 1:2, although they evidently contain the same amounts of DNA and are consequently both diploid. Similarly, in previous studies it has been found that the geometric series of nuclear volumes in the testis of Arvelius (Schrader and Leuchtenberger [1950]) and in developing mouse eggs (Alfert [1950]) are not correlated with corresponding differences in chromosome or DNA content. The doubling of nuclear volumes in uterine glands of castrate mice under influence of estrogen (Salvatore [1950]) also is not accompanied by an increase of nuclear DNA content ).…”
Section: Discussionmentioning
confidence: 99%